Sleep Disorders, Sleeping Pills and Hypertension: A Systematic Review: Pharmaceutical Sciences-Psychology for curing mental health - Alrimi, Sara Khalid; Aljeffry, Raghad Abdulrahman; Isa, Raghad Ishag; Bokhari, Rawah Mohammad; Elashmony, Sahar; Fairaq, Arwa; Hindi, Yosra Al- (International Journal of Life Science and Pharma Research, 2021)
Hypertension and insomnia or sleep loss is very common and often co-exists together. There are evidences suggesting that the increase in the prevalence of arterial hypertension in the past decade might be related both to an increased prevalence of insomnia and to the decline of sleep duration due to modern lifestyle. However, there is a lack of studies in detailed investigation of the effect of sleeping pills on blood pressure. The aim of this study was to reconsider both the clinical evidence of the relationship between conditions of sleep loss, sleeping pills, and hypertension and the potential pathophysiological mechanisms underlying the biological plausibility of their relationship. Through a systematic search from MEDLINE, EMBASE, and PubMed, we selected 20 articles, which reported sleep disorders, or studied sleep duration or insomnia and sleeping pills and their relationship with blood pressure or hypertension in participants over 18 years. Sleep loss or sleep disorders due to persistent insomnia or sleep apnea seems to be associated with an increased risk for hypertension, even after controlling for other hypertensive risk factors. For sleeping pills, it is still a controversy whether they increase or decrease blood pressure in patients with sleeping disorders. Chronic sleep loss or alterations of sleep quality can act as a physiological stressor or that impairs brain functions and contributes to hypertension. However, further studies need to measure the relationship between sleeping pills and blood pressure.